THE DEVELOPMENT OF STEM EDUCATION IN UZBEKISTAN'S EDUCATIONAL SYSTEM - Ablizova Gulzahiryam Alimovna,; Aripova Gulchehra Ishankulovna,; Umarova Nadira Raxmanovna, (INTEGRATION OF EDUCATION AND SCIENCE: GLOBAL CHALLENGES AND SOLUTIONS, 2026)
This article explores the development of STEM education in Uzbekistan’s educational system, highlighting recent policy reforms, curriculum modernization, teacher training initiatives, and infrastructural improvements. It examines the progress made in increasing student participation in science, technology, engineering, and mathematics disciplines, while also identifying challenges such as regional disparities, resource limitations, and the need for stronger collaboration between educational institutions and industry. The study concludes that sustained investment and policy support are crucial to fully realize the potential of STEM education as a driver for Uzbekistan’s socio-economic growth and technological innovation.